Effects of formononetin on the expression of orexin and calcitonin gene-related peptide genes in a stress model rats - Elaheh Basirat; Fraiba Mahmoudi; Homayoun Khazali (مجله دانشگاه علوم پزشکی بیرجند)
Background and Aims: Formononetin is a flavonoid compound derived from various plants, such as red clover. Calcitonin gene-related peptide (CGRP) and Orexin are among the important neuropeptides in the hypothalamus in controlling stress responses. Moreover, previous studies have indicated the anti-stress effects of formononetin. However, its molecular mechanism has not yet been elucidated. The present study aimed to evaluate the effect of formononetin on the hypothalamic expression of CGRP and HCRT (the hypocretin neuropeptide precursor) in a rat model of stress. Materials and Methods: In this experimental study, 20 male Wistar rats weighing 200±10 g were divided into four groups (n=5 for each group). For stress induction, rats were placed in a restraint cage for 2 h. Formonontin with 20 µg and 40 μg doses was injected in a single dose with a volume of 3 μl via the third cerebral ventricle. Then, the hypothalamic samples were removed, and real-time polymerase chain reaction (RT-PCR) was performed to measure gene expression. Results: In the stress rat model, the expression of CGRP and HCRT genes significantly decreased compared to the control group (P≤0.01). The injection of formononetin significantly decreased the expression of CGRP and HCRT genes compared to stress model rats (P≤0.01). Conclusion: The present study indicated the anti-anxiety effects of formononetin. The anxiolytic effects of formononetin may be exerted by down-regulating the function of the stress-related neurons in the hypothalamus.